Vakuum in plazma v zemeljski atmosferi - Čekada, Miha (Vakuumist, 2001)
In this paper, the compositions and structure of Earth atmosphere is described. Empahsis is given on the chemical reactions in stratosphere and ionosphere, the vacuum environment in the area where manned spacecraft orbit, as well as examples of plasma in nature.
Keywords: Zemlja; Zemlya; atmosfera; struktura; vakuum; plazma